Exploring the combined effects of the Arctic Oscillation and ENSO on the wintertime climate over East Asia using self‐organizing maps. Issue 17 (7th September 2017) - Huang, Wenyu; Chen, Ruyan; Yang, Zifan; Wang, Bin; Ma, Wenqian
Abstract: To examine the combined effects of the different spatial patterns of the Arctic Oscillation (AO)‐related sea level pressure (SLP) anomalies and the El Niño–Southern Oscillation (ENSO)‐related sea surface temperature (SST) anomalies on the wintertime surface temperature anomalies over East Asia, a nonlinear method based on self‐organizing maps is employed. Investigation of identified regimes reveals that the AO can affect East Asian temperature anomalies when there are significant SLP anomalies over the Arctic Ocean and northern parts of Eurasian continent. Analogously, ENSO is found to affect East Asian temperature anomalies when significant SST anomalies are present over the tropical central Pacific. The regimes with the warmest and coldest temperature anomalies over East Asia are both associated with the negative phase of the AO. The ENSO‐activated, Pacific‐East Asian teleconnection pattern could affect the higher latitude continental regions when the impact of the AO is switched off. When the spatial patterns of the AO and ENSO have significant, but opposite, impacts on the coastal winds, no obvious temperature anomalies can be observed over south China. Further, the circulation state with nearly the same AO and Niño3 indices may drive rather different responses in surface temperature over East Asia. The well‐known continuous weakening (recovery) of the East Asian winter monsoon that occurred around 1988 (2009) can be attributed to the transitions of the spatial patterns of the SLP anomalies over the Arctic Ocean and Eurasian continent, through their modulation on the occurrences of the Ural and central Siberian blocking events. Key Points: A nonlinear method for studying the combined effects of two phenomena on the third phenomenon is proposed A composite analysis based on spatial patterns is more reliable than that based on indices The abrupt transitions in the EAWM are closely related to the spatial patterns of the AO‐related SLP anomalies